An analysis of intraoperative recall of awareness in Thai Anesthesia Incidents Study (THAI Study) - Mali Rungreungvanich (2018)
Objectives: This study aimed to analyze intraoperative awareness using database of Thai Anesthesia Incidents Study (THAI Study) with regard to frequency, contributing factors, preventive and corrective strategies. Material and Method: Details of intraoperative recall of awareness were recorded prospectively by attending anesthesiologists or nurse anesthetists in standardized record forms during February 1,2003 to July 31, 2004. Participating hospitals included 7 university hospitals, 5 tertiary care hospitals, 4 secondary care hospitals, and 4 primary care hospitals. All data were analyzed to identify contributing factors, preventive and corrective strategies. Results: Among 126078 general anesthetized cases, there were 99 cases of intraoperative recall of awareness. Awareness was found in female patients more than male patients (63% versus 37%). The majority of patients had ASA PS 1 and 2. Cardiac, obstetric, and lower abdominal surgery were involved in anesthesia awareness more than other type of surgery. Patients experiencing awareness reported sound (62%), pain (51%), feeling operated without pain (33%), and paralysis (25%). There was slight impact of anesthesia awareness in Thai patients (only 13% had temporary emotional stress and 13% had mild anxiety) despite small percentage of proper management by reassurance and psychiatric consultation (15%). The contributing factors included inadequate knowledge (67%), inadequate medication dosage (44%), and inadequate care from inexperience (11%). Awareness incidents were documented to be preventable in 36% of patients and partially preventable in 38 % of patients. The corrective strategies included guideline practice (30%), additional training (28%), quality assurance activity (19%), and improved supervision (16%). Conclusion: The incidence of intraoperative recall of awareness in this study was 0.08%. Patients reported sound, pain, feeling operated without pain, and paralysis. Corrective strategies included guideline practice, additional training, quality assurance activity, and improved supervision.